Sistema de tratamiento de aguas residuales y su incidencia en la calidad de los efluentes de la parroquia Moraspungo del cantón Pangua, Provincia de Cotopaxi. Año 2015. Propuesta de optimización del sistema sanitario. - Suárez Ayoví, Katherine (2015)
In this research the quality of discharges (effluents) and efficiency Treatment Plants Wastewater located in the urban area of the Moraspungo Parish and Recinto Las Juntas was determined. The identification of environmental impacts according to their importance in the area of influence of each plant allowed to determine that the environmental effects are of a significance level of moderate to severe, reflecting the efficiency of wastewater treatment plants is mostly water compromised by social and environmental damages, a situation which was verified to assess the attributes and verify the actual state pollutant in situ effluent treatment system. To determine the quality of the effluent in the four plants were analyzed fourteen different parameters, however the most representative and disturbing the treatment process is in wastewater treatment relative deficiency of pathogens; thus the microbiological analysis of effluent (output) relative to total and fecal coliforms was outside the permissible limit NM 10000 / 100ml with average values was NM 481500 / 100ml. The lack of technical procedures, the lack of an environmental culture to pour liquid waste collection system health and non-availability of alternatives to improve the system because of the topography and location of the plants are other causes that affect treatment system. This is corroborated by statistical analysis allowed to validate the alternative hypothesis concerning the inefficiency and propose the restructuring and relocation of plants treating Moraspungo parish, Canton Pangua, Cotopaxi Province.